The beneficial effects of a water-based aerobic exercise session on the blood lipids of women with dyslipidemia are independent of their training status - Costa, Rochelle Rocha (Clinics (Sao Paulo), 2020)
OBJECTIVES: To evaluate the acute effects of a session of water-based aerobic exercise on the blood lipid levels of women with dyslipidemia and to compare these results according to their training status. METHOD: Fourteen premenopausal women with dyslipidemia, aged 40–50 years, participated in two water-based aerobic exercise sessions, the first when they were generally sedentary and the second after they were trained with a water-based aerobic training program for 12 weeks. Both experimental sessions were performed using the same protocol, lasted 45 min, and incorporated an interval method, alternating 3 min at a rating of perceived exertion (RPE) of 13 and 2 min at an RPE of 9. Total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and lipoprotein lipase enzyme (LPL) were obtained through venous blood collection before and immediately after each session. A generalized estimating equation method and Bonferroni tests were conducted (with time and training status as factors) for statistical analyses. RESULTS: At enrollment, the mean age of the participants was 46.57 years (95% confidence interval [CI] 44.81−48.34). The statistical analyses showed a significant time effect for all variables (TC: p=0.008; TG: p=0.012; HDL: p<0.001; LPL: p<0.001) except for LDL (p=0.307). However, the training status effect was not significant for any variable (TC: p=0.527; TG: p=0.899; HDL: p=0.938; LDL: p=0.522; LPL: p=0.737). These results indicate that the TC and TG levels reduced and the HDL and LPL concentrations increased from pre- to post-session in similar magnitudes in both sedentary and trained women. CONCLUSIONS: A single water-based aerobic exercise session is sufficient and effective to beneficially modify the lipid profile of women with dyslipidemia, regardless of their training status.